Jobst Welge. Genealogical Fictions: Cultural Periphery and Historical Change. Baltimore: Johns Hopkins UP, 2015. - Patrick R Young (Studies in 20th & 21st Century Literature, 2016)
Review of Jobst Welge. Genealogical Fictions: Cultural Periphery and Historical Change. Baltimore: Johns Hopkins UP, 2015.
Keywords: Welge